2017
DOI: 10.1111/nph.14936
|View full text |Cite
|
Sign up to set email alerts
|

Independent signalling cues underpin arbuscular mycorrhizal symbiosis and large lateral root induction in rice

Abstract: Perception of arbuscular mycorrhizal fungi (AMF) triggers distinct plant signalling responses for parallel establishment of symbiosis and induction of lateral root formation. Rice receptor kinase CHITIN ELICITOR RECEPTOR KINASE 1 (CERK1) and α/β-fold hydrolase DWARF14-LIKE (D14L) are involved in pre-symbiotic fungal perception. After 6 wk post-inoculation with Rhizophagus irregularis, root developmental responses, fungal colonization and transcriptional responses were monitored in two independent cerk1 null mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 24 publications
(63 reference statements)
1
38
0
Order By: Relevance
“…These two proteins have been implicated in promoting germination, hypocotyl elongation, light response, reducing hyponasty, establishing arbuscular mycorrhizal fungal (AMF) symbiosis, affecting leaf morphology and drought resistance (Nelson et al ., ; Sun and Ni, ; Waters et al ., ; Stanga et al ., ; Gutjahr et al ., ; Li et al ., ; Lee et al ., ). Root‐related phenotypes reported for any mutant deficient in KAI2 include the absence of AMF symbiosis in rice (Gutjahr et al ., ) and a lower large LRD in rice (Chiu et al ., ). The AMF symbiosis seems to be impaired in the early stages of the interactions as no physical contact between plant and fungus or gene expression changes generally triggered by fungal signals could be found.…”
Section: Discussionmentioning
confidence: 97%
“…These two proteins have been implicated in promoting germination, hypocotyl elongation, light response, reducing hyponasty, establishing arbuscular mycorrhizal fungal (AMF) symbiosis, affecting leaf morphology and drought resistance (Nelson et al ., ; Sun and Ni, ; Waters et al ., ; Stanga et al ., ; Gutjahr et al ., ; Li et al ., ; Lee et al ., ). Root‐related phenotypes reported for any mutant deficient in KAI2 include the absence of AMF symbiosis in rice (Gutjahr et al ., ) and a lower large LRD in rice (Chiu et al ., ). The AMF symbiosis seems to be impaired in the early stages of the interactions as no physical contact between plant and fungus or gene expression changes generally triggered by fungal signals could be found.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it fails to induce lateral roots in response to AMF (Chiu et al, 2018). However, root colonization of oscerk1 is only delayed and not entirely abolished (Miyata et al, 2014;Zhang et al, 2015;Chiu et al, 2018), pointing towards redundant recognition mechanisms. By contrast, OsCEBiP, a LysM RLP, which acts as co-receptor of OsCERK1 in the perception of longchain chitin oligomers from pathogenic fungi (Kaku et al, 2006), is not required for the AM symbiosis and is not essential for Myc-COinduced Ca 2+ spiking (Carotenuto et al, 2017).…”
Section: Fungal Chitin-based Molecules Elicit Symbiotic Plant Responsesmentioning
confidence: 97%
“…The rice LysM RLK OsCERK1, which has a dual role in both interactions with pathogenic fungi and AMF (Miyata et al, 2014), was shown to play a central role in the perception of Myc-COs because an oscerk1 mutant does not respond to these molecules with Ca 2+ -spiking (Carotenuto et al, 2017). In addition, it fails to induce lateral roots in response to AMF (Chiu et al, 2018). However, root colonization of oscerk1 is only delayed and not entirely abolished (Miyata et al, 2014;Zhang et al, 2015;Chiu et al, 2018), pointing towards redundant recognition mechanisms.…”
Section: Fungal Chitin-based Molecules Elicit Symbiotic Plant Responsesmentioning
confidence: 99%
“…The karrikin signaling component DWARF 14-LIKE (D14L) is required for colonization of rice roots by AM fungi (Gutjahr et al, 2015b). The D14L-mediated pathway may act in parallel with the CERK1-dependent pathway (Gutjahr et al, 2015b;Chiu et al, 2018). Moreover, the mesocotyls of the d3 mutant are longer than those of other SL pathway mutants, including d10 and d14 (Hu et al, 2010), and loss of function of D14L increases mesocotyl length in the dark (Gutjahr et al, 2015b;Kameoka and Kyozuka, 2015).…”
Section: Introductionmentioning
confidence: 99%